Front Cover. Issue 4 (April 2017) - Redfern, Jessica V.; Moore, Thomas J.; Fiedler, Paul C.; de Vos, Asha; Brownell, Robert L.; Forney, Karin A.; Becker, Elizabeth A.; Ballance, Lisa T.
Abstract : The cover image, by Jessica V. Redfern et al ., is based on the Biodiversity Research Predicting cetacean distributions in data‐poor marine ecosystems, DOI:10.1111/ddi.12537 . Photo Credit: Asha de Vos.